A clinical comparison on the plaque removal efficiency of powered and manual toothbrushes as used by visually impaired grade 5-6 elementary and 1st - 4th year high school students of Philippine National School for the blind, aged 11-20 - Dela Cruz, Rodaline; Dela Rosa, Juliet; Mendoza, Michael Antonio F. (Adviser).; Philippine National School for the blind
This study was done among visually impaired grade 5-6 elementary and 1st - 4th year high school students of Philippine National School for the Blind (aged 11-20). This was carried out primarily to compare the efficiency of powered and manual toothbrushes in plaque removal as used by persons with visual impairment. Fifty-one (51) students of the mentioned school were included and 59 of them completed the research protocol. Inclusion interviews were done in the dental clinic of the school followed by clinical examination and trial under the supervision of the school dentist. A crossover single-blind type of experimental study was used wherein all the participants used the powered and manual toothbrushes with the single examiner unaware of what brush type each participant used. The pre-test and post-test plaque indices were evaluated using Rustogi Modified Navy Plaque Index. Data analysis revealed that there is a significant difference on plaque removal efficiency of powered toothbrush compared to a manual toothbrush on the whole mouth, gumline and interproximal areas of visually impaired students of Philippine National School for the Blind aged 11-20.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Toothbrushes; Dental therapeutics; Children with visual disabilities